A comparison between pre-sleep heart rate variability biofeedback and electroencephalographic biofeedback training on sleep in national level athletes with sleep disturbances - Li, Q.; Shi, M.; Steward, C. J.; Che, K.; Zhou, Y. (Applied Psychophysiology and Biofeedback, 2024)
The current study compared the effects of heart rate variability biofeedback (HRV-BF) and electroencephalographic biofeedback (EEG-BF) on sleep, mood, and reaction time. Fourteen highly trained male athletes with sleep disturbances participated in this randomised crossover study. Participants took part in HRV-BF and EEG-BF training, with each condition consisting of eight sessions over 15 days. Polysomnography (PSG) and the Pittsburgh sleep quality index (PSQI) were used to assess sleep quality, the profile of mood states (POMS) questionnaire to monitor mood, and reaction time to measure performance pre and post intervention. HRV-BF training improved PSG sleep efficiency (SE) (P = 0.022, d = 0.35, 95% CI 0.01 to 0.16) and subjective sleep duration (P = 0.011, ES = 0.40) when compared to EEG-BF. Only HRV-BF reduced reaction time pre to post biofeedback training (P = 0.020, d = 0.75, 95% CI 0.006 to 0.059). The PSQI showed that both HRV-BF (P = 0.025, ES = 0.31) and EEG-BF (P = 0.003, ES = 0.32) resulted in improved global PSQI scores. Total mood disturbance was also reduced though HRV-BF (P = 0.001, ES = 0.40) and EEG-BF (P = 0.001, ES = 0.30). HRV-BF and EEG-BF enhanced some subjective parameters of sleep and mood. HRV-BF increased PSG SE and subjective sleep duration more than EEG-BF in highly trained athletes with sleep disturbances.